Improved ORR Activity and Long-Term Durability of Pt Nanoparticles Deposited on TiO2-Decorated Multiwall Carbon Nanotubes. Issue 16 (3rd December 2019) - Hussain, Sajid; Erikson, Heiki; Kongi, Nadezda; Tarre, Aivar; Ritslaid, Peeter; Kook, Mati; Rähn, Mihkel; Merisalu, Maido; Sammelselg, Väino; Tammeveski, Kaido
Abstract : Titanium dioxide coatings of different thicknesses were deposited on the acid-treated multiwall carbon nanotubes (MWCNTs) using controlled atomic layer deposition (ALD). Pt nanoparticles (NP) were deposited on TiO2 /MWCNT supports using two deposition methods, viz. sputter-deposition and photo-deposition. Scanning electron microscopy (SEM) and scanning transmission electron microscopy (STEM) measurements revealed successful application of ALD for the deposition of TiO2 . Both magnetron sputtering and photo-deposition were found to be efficient and well-controlled techniques for the deposition of Pt NPs on oxide-carbon support. Electrochemical decontamination and characterization of the catalysts surface was carried out by CO stripping and cyclic voltammetry in 0.1 M KOH solution. The prepared Pt-TiO2 /MWCNT catalyst showed comparable oxygen reduction reaction (ORR) activity to that of commercial Pt/C (20 wt%), while long-term durability test revealed better durability of the prepared catalysts due to strong metal-support interaction.